The Dynamics and Complexities of Interracial Gay Families in South Africa: A New Frontier Gay Relationships in South Africa - Adeagbo, Oluwafemi (SpringerBriefs in Sociology, 2019)
This book provides an in-depth account of a qualitative study on the familial arrangements and domestic settings shaping interracial gay partnerships in the South African context, and it offers both empirical and theoretical insights on the topic. While heterosexual intimate relationships, particularly mixed-race couples, have attracted societal and scholarly attention in South Africa due to the country's past history of racial segregation, it is, however, striking how little emphasis is placed on understanding same-sex unions in a transforming South Africa. This book is timely and important because it explores the vignettes, complexities and dynamics of interracial gay intimate relationships, an area that hardly gets the scholarly attention it deserves. The book addresses the intersectionality, and the question of how sexuality, gender, racial identity and personal resources influence the relationship as well as the way resilience strategies are drawn upon to sustain the partnership.